The importance of non-data touching processing overheads in TCP - Kay, Jonathan (Computer communication review.)
We present detailed measurements of various processing overheads of the TCP/IP and UDP/IP protocol stacks on a DECstation 5000/200 running the Ultrix 4.2a operating system. These overheads include data-touching operations, such as the checksum computation and data movement, which are well known to be major time consumers. In this study, we also considered overheads due to non-data touching operations, such as network buffer manipulation, protocol-specific processing, operating system functions, data structure manipulations (other than network buffers), and error checking. We show that when one considers realistic message size distributions, where the majority of messages are small, the cumulative time consumed by the non-data touching overheads represents the majority of processing time. We assert that it will be difficult to significantly reduce the cumulative processing time due to non-data touching overheads.